Role Of Ulama And Community In Overseeing Developments Tourism In The Pantai Cermin Area Serdang Bedagai District - Tika Riani Yusuf; Annaisaburi Nasution (LPPM Universitas Trunojoyo Madura, 2023)
The purpose of this study was to find out the role of Islamic scholars and the community in supervising the development of tourism spots in the pantai Cermin area, Serdang Bedagai Regency. In this study, the researcher used a descriptive qualitative method, by obtaining direct data from informants who represented all sources regarding the role of Islamic scholars and the community in supervising tourist attractions in the pantai Cermin area, Serdang Bedagai Regency. The purpose of the researchers chose this research method because it was based on the objectives and research problems. The data collection techniques used in this study were interview techniques and observation techniques. The results of this study are the role of the clergy at the pantai cermin in supervising tourist attractions related to religious norms in pantai Cermin district, Serdang Bedagai Regency.What the clergy did was just to appeal and there were no sanctions or punishments imposed on violators of the norms who visited these tourist spots, especially in the pantai Cermin area, Serdang Bedagai Regency. Likewise with the surrounding community, especially those who live in coastal tourism areas, they lack supervision or urge tourists not to violate religious norms, both in terms of the visiting hours of tourists who come to the beaches on the pantai cermin, Serdang Bedagai.Pantai cermin is the majority of the population who are Muslim and uphold religious values. Therefore, the clergy and the community should mutually maintain order in the beach so as to avoid unwanted incidents. As a source of community empowerment, there are also factors that hinder the community from conducting surveillance on tourist objects in the sub-district of pantai Cermin, namely because there are several beaches that are managed privately where some people who sell at these tourist attractions do not dare to participate in supervising them for fear of not being able to trade. On these beaches such as sustainable Bali beaches, Pondok Indah beaches, etc. Lack of professional public awareness in carrying out supervision. Some people still don't care about supervision.